2019
DOI: 10.1108/ijsi-07-2018-0044
|View full text |Cite
|
Sign up to set email alerts
|

The effects of residual stresses and strains on lateral-torsional buckling behavior of cold-formed steel channel and built-up I-sections beams

Abstract: Purpose The purpose of this paper is to focus on the influences of residual stresses which were induced during roll-forming sections on lateral-torsional buckling of thin-walled cold-formed steel channel and built-up I-sections beams. Built-up I section is made up of two back-to-back cold-formed channel beams. In this direction, at the primary stage, the roll-forming process of a channel section was simulated in ABAQUS environment and the accuracy of the result was verified with those existing experiments. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Similar to square hollow steel sections, the through‐thickness residual stress variations for RHS showed nonlinear distributions. According to previous studies, the magnitude of tensile residual stress decreases as the width to radius ratio decreases 4,23,25,36,37 . Therefore, the RHS presented in this study possessed a relatively lower magnitude of longitudinal residual stresses than the SHS.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Similar to square hollow steel sections, the through‐thickness residual stress variations for RHS showed nonlinear distributions. According to previous studies, the magnitude of tensile residual stress decreases as the width to radius ratio decreases 4,23,25,36,37 . Therefore, the RHS presented in this study possessed a relatively lower magnitude of longitudinal residual stresses than the SHS.…”
Section: Resultssupporting
confidence: 65%
“…Heinilä et al 22,24 studied the impacts of the residual stresses on fatigue of circular and rectangular cross-sections by conducting experiments and numerical modeling of the cold forming process. In the same way, the study conducted by Kabir and Parvizi 25 showed that residual stress effect on lateral-torsional buckling behavior is very significant. Experimental fatigue tests of Heinilä 22,24 further showed that square hollow section's corner areas are more susceptible to fracture than the flat areas.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations